2017
DOI: 10.3102/0013189x17732753
|View full text |Cite
|
Sign up to set email alerts
|

Does Test Preparation Mean Low-Quality Instruction?

Abstract: Critics of test-based accountability warn that test preparation has a negative influence on teachers' instruction due to a focus on procedural skills. Others advocate that the adoption of more rigorous assessments may be a way to incentivize more ambitious test preparation instruction. Drawing on classroom observations and teacher surveys, we do find that test preparation activities predict lower quality and less ambitious mathematics instruction in upper-elementary classrooms. However, the magnitudes of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Non-availing epistemic beliefs about mathematics-i.e., the belief that knowledge is fixed, simple, certain, objective, and comes from a person of authority in mathematics rather than seeing the discipline of mathematics as evolving, complex, and uncertain at times-were found to be positively associated with higher student mathematics achievement. This may be due to the way the standardized mathematics assessments were constructed (more factual than cognitively rich test questions; Popham, 2001) and teachers' reflexive strategies (i.e., test preparation) against high-stakes testing that may result in less availing views of mathematics and less ambitious teaching of mathematics (Blazar & Pollard, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Non-availing epistemic beliefs about mathematics-i.e., the belief that knowledge is fixed, simple, certain, objective, and comes from a person of authority in mathematics rather than seeing the discipline of mathematics as evolving, complex, and uncertain at times-were found to be positively associated with higher student mathematics achievement. This may be due to the way the standardized mathematics assessments were constructed (more factual than cognitively rich test questions; Popham, 2001) and teachers' reflexive strategies (i.e., test preparation) against high-stakes testing that may result in less availing views of mathematics and less ambitious teaching of mathematics (Blazar & Pollard, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Menken (2006) showed that teachers in bilingual programs shifted to English instruction in the grades in which content assessments went into effect due to test administration in English. High stakes test preparation can dilute instruction (Blazar & Pollard, 2017), a phenomenon that Palmer and Snodgrass Rangel (2011) found to impact EL students as teachers felt that test preparation resulted in a narrowing of instruction that was at odds with EL students' pedagogical and linguistic needs. These concerns come alongside doubt that the use of high-stakes content area assessments translates into improved learning overall (Amrein & Berliner, 2002), and doubt about the degree to which instructional alignment with state academic standards is related to effective teaching (Polikoff & Porter, 2014).…”
Section: Policy Area #2: El Assessmentmentioning
confidence: 99%
“…Test-based accountability, and especially test preparation activities that have arisen from it, also change the nature of instruction and are associated with math teaching that is of lower quality and less rigorous (Blazar & Pollard, 2017). Instruction is modified by the interim assessment results that have now become a dominant feature of classrooms (Clune & White, 2008).…”
Section: Measuring Achievement and Opportunitymentioning
confidence: 99%